Epoprostenol for very low birth weight (VLBW) infants: a novel dilution protocol - S. Rugolotto; R. Beghini; I. Cogo; G. Sidoti; E.M. Padovani; A. Pietrobelli (PAGEPress Publications, 2013)
Epoprostenol has been the first effective treatment for severe pulmonary arterial hypertension. Epoprostenol is provided in vials for adult therapy. To our knowledge there are no reports on specific dilution protocols for epoprostenol in VLBW infants, when very small infusion rates are required. We describe the dilution protocol we applied to a preterm infant who was born at 30 weeks of gestational age with a weight of 1.000 g. Our dilution protocol keeps the recommended dilution ratios, and the required solution pH, for very small dosages of epoprostenol, using the same diluent vial. Our method allows a correct and safe administration of epoprostenol in VLBW infants.